Analisis Faktor-Faktor yang Mempengaruhi Industrialisasi di ASEAN Tahun 2009-2023 - Asy Syifa Rizki Utami; Fitrah Sari Islami; Yustirania Septiani (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
Industrialization plays a crucial role in the economy as it is widely regarded as a key development strategy for achieving high economic growth and sustainable development. However, the contribution of the industrial sector to Gross Domestic Product (GDP) in the ASEAN region has tended to decline following the 2008 global financial crisis. This study aims to evaluate the effects of Foreign Direct Investment (FDI), domestic credit, human capital, and trade openness on the industrialization process in six ASEAN countries over the period 2009–2023. The research employs a descriptive analysis combined with a quantitative approach using a dynamic panel data model. The findings reveal that FDI and trade openness have a positive and significant impact on industrialization, while domestic credit exerts a negative and significant effect. Meanwhile, human capital shows a negative but statistically insignificant influence on industrialization. The novelty of this study lies in its use of recent post-crisis data and a dynamic panel framework to simultaneously assess financial, human capital, and trade factors in explaining the declining trend of industrialization in ASEAN countries. Therefore, governments in the six ASEAN countries need to strengthen financial sector regulation and supervision to maintain stability and anticipate potential crises that may hinder the pace of industrialization.